A Comparison of Brunt’s Criteria, the Non-Alcoholic Fatty Liver Disease Activity Score (NAS), and a Proposed NAS Scoring that Includes Fibrosis in Non-Alcoholic Fatty Liver Disease Staging - Santiago-Rolón, Amarilys; Purcell, Dagmary; Rosado, Kathia; Toro, Doris H. (Puerto Rico Health Sciences Journal, 2015)
Objective: The aim of this study was to determine the prevalence of NASH in veterans with metabolic syndrome and compare histologic grading using the Brunt criteria, the NAFLD activity score (NAS), and a proposed NAS scoring system that has been modified to include fibrosis staging. Methods: Veterans with metabolic syndrome, hepatic steatosis, and elevated ALT and AST levels and who underwent liver biopsies from 2004 through 2010 were included in this study. Biopsies were evaluated by a single hepatopathologist. Each biopsy was analyzed using the Brunt criteria, the NAS system, and the NAS system plus fibrosis staging. Results: Sixty patients having a mean age of 50.4 (±12.8 years) were included in the study; 88.3% were men. Fifty percent met criteria according to the Brunt system. When biopsies were classified using the NAS system, only 30.0% (18/60) were found to have a score of 5 or more, while, when adding fibrosis staging, the number of patients with a score of 5 or more increased to 33 (55.0%). Upon evaluating the predictive ability of the NAS scoring system, we found that when including fibrosis staging we obtained a higher sensitivity (86.7% vs. 40.0%) and a lower specificity (76.7% vs. 80.0%). Conclusion: In our population of patients with metabolic syndrome about 50 to 55% had steatohepatitis. There were significant differences between the scoring systems. When our NAS plus fibrosis system was used, more patients were recognized and the sensitivity increased. Further validation studies are required to evaluate this proposed modified NAS scoring system.